“ANALISIS PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SHAMPO PANTENE DI KOTA WATES ” - SALIM MAGHFUR (JURNAL EKOBIS DEWANTARA, 2018)
This study aims to analyze the effect of product quality on purchasing decisions, price to buyer decisions, promotion of buyer decision, and product quality, price, promotion together influence on purchasing decision of pantene shampoo in Wates City Yogyakarta. The population in this research is the consumer of Pantene Shampoo in Yogyakarta City examined by the writer include Product Quality (X1), Price (X2), Promotion (X3) and Purchase Decision (Y). The sample of the study was 100 consumers who used Pantene Shampoo in Wates City. Data collection method used questionnaire method, while data analysis technique used multiple regression analysis supported by T test and F test and classical assumption test consist of normality test, multicollinearity test, and heterokedastisity test. Result of research with 5% or 0,05 significance level indicates that product quality significantly influence purchasing decision (0.000 <0,05), price have significant effect to purchasing decision (0.000 <0,05), and promotion has significant effect to purchasing decision 0.000 <0.05). Simultaneously variable of product quality, price and promotion have a significant effect to purchasing decision of prodak shampoo pantene in Wates city of Yogyakarta.